THE EFFECT OF DIGITALIZATION SKILLS ON EMPLOYEE PERFORMANCE WITH READINESS TO CHANGE AS AN INTERVENING VARIABLE - Endarti Endarti; Faizal Mulia Z; Nor Norisanti (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The digital revolution has encouraged companies to carry out technological transformation to improve operational efficiency and effectiveness. However, the implementation of digitalization does not always have a direct impact on improving employee performance. This study aims to analyze the effect of digitalization skills on employee performance with readiness to change as a mediating variable at PT Sari Alam Sukabumi. The research method used is quantitative with a sample size of 122 respondents. Data collection was conducted using questionnaires distributed to employees, and data analysis techniques employed Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results showed that digitalization skills have a positive and significant effect on employee performance. In addition, readiness to change has a positive and significant effect on employee performance. Furthermore, the study found that readiness to change successfully mediates the relationship between digitalization skills and employee performance. This indicates that employees who possess strong digital competencies and are ready to adapt to organizational changes are more likely to demonstrate improved performance. These findings highlight the importance of developing digital skills and fostering a culture of change readiness to support successful digital transformation in organizations.